ORGANIZATION OF TECHNOLOGY LESSONS IN SECONDARY SCHOOLS - Olimov Bakhtiyorjon Usmonovich; Ikromova Mubinakhon Hakimjon qizi (Galaxy International Interdisciplinary Research Journal, 2021)
This article covers how to prepare students for Handicrafts, about Handicrafts based on their interests, inclinations and opportunities. In this regard, the process of Handicrafts Education is aimed at developing knowledge, Handicrafts, ethics, aesthetic economic-environmental and intellectual opportunities for this age in the students in specific Handicrafts processes, as a result of which the preparation of them for Handicrafts in the process of Handicrafts creates the necessary linkage for children to continue working with natural and artificial raw materials.